Magnetic shielding of an inhomogeneous magnetic field source by a bulk superconducting tube. (2nd February 2015) - Hogan, K; Fagnard, J-F; Wéra, L; Vanderheyden, B; Vanderbemden, P
Abstract: Bulk type-II irreversible superconductors can act as excellent passive magnetic shields, with a strong attenuation of low frequency magnetic fields. Up to now, the performances of superconducting magnetic shields have mainly been studied in a homogenous magnetic field, considering only immunity problems, i.e. when the field is applied outside the tube and the inner field should ideally be zero. In this paper, we aim to investigate experimentally and numerically the magnetic response of a high- T c bulk superconducting hollow cylinder at 77 K in an emission problem, i.e. when subjected to the non-uniform magnetic field generated by a source coil placed inside the tube. A bespoke 3D mapping system coupled with a three-axis Hall probe is used to measure the magnetic flux density distribution outside the superconducting magnetic shield. A finite element model is developed to understand how the magnetic field penetrates into the superconductor and how the induced superconducting shielding currents flow inside the shield in the case where the emitting coil is placed coaxially inside the tube. The finite element modelling is found to be in excellent agreement with the experimental data. Results show that a concentration of the magnetic flux lines occurs between the emitting coil and the superconducting screen. This effect is observed both with the modelling and the experiment. In the case of a long tube, we show that the main features of the field penetration in the superconducting walls can be reproduced with a simple analytical 1D model. This model is used to estimate the maximum flux density of the emitting coil that can be shielded by the superconductor.